The Effect of Profitability and Operating Cash Flow on Financial Distress with Firm Value as a Mediating Variable - Dwi Rara Al Munawaroh; Wiralestari Wiralestari; Nela Safelia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Technology sector companies are known for rapid innovation but also face high uncertainty, which is likely to cause financial distress. In Indonesia, several technology firms publicly traded on the Indonesia Stock Exchange (IDX) experienced declining profitability and negative operating cash flows during the 2021–2023 period. The aim of this research is to examine the influence of profitability and operating cash flow on financial distress, with firm value as an intervening variable. The research addresses inconsistencies in financial indicators—declining profits do not always indicate financial distress, especially when firm value is not taken into account. Using secondary data from annual reports and the Investing website, this study makes use of a quantitative method involving path analysis. A purposive sampling technique resulted in 78 firm-year observations. Data analysis was carried out using SPSS software. It was found that both firm value is positively and significantly affected by profitability and operating cash flow. However, only operating cash flow and firm value have a statistically significant positive relationship with financial distress, unlike profitability. Furthermore, firm value does not mediate the relationship between profitability and financial distress but does mediate the relationship between operating cash flow and financial distress. These findings suggest that operating cash flow is a more reliable indicator than profitability in predicting financial distress and emphasize the mediating role of firm value in financial instability.